Multidisciplinary Care of the Patient with Chronic Obstructive Pulmonary Disease - Kuzma, Anne Marie (American Thoracic Society, 2008)
The National Emphysema Treatment Trial used a multidisciplinary team approach to implement the maximum medical care protocol, including adjustment of medications and outpatient pulmonary rehabilitation for all patients and nutritional and psychological counseling as needed. This article discusses the benefits of such an approach in the care of the patient with chronic obstructive pulmonary disease. Team member roles complement each other and contribute to the goal of providing the highest-quality medical care. The primary focus of the team is to reinforce the medical plan and to provide patient education and support. This article reviews the elements of the initial patient assessment and the functional and nutritional assessment. Patient education focuses on medication use, recognition and management of chronic obstructive pulmonary disease exacerbation symptoms, smoking cessation, advance directives, and travel.